The prognostic importance of double-expressor subgroup and AID, UNG and mismatch repair protein expressions in diffuse large B-cell lymphomas - BOZKURT, SÜHEYLA; ELİBOL, TAYFUN (MARMARA UNIV, FAC MEDICINE, 2020)
Objective: The cases of diffuse large B-cell lymphoma, (DLBCL not otherwise specified (NOS)) which immunohistochemically exhibit MYC and BCL2 expressions arc defined as double-expressor lymphomas (DELs). This study aimed to assess the prognostic impact of DEL and the expressions of other proteins that may have role in tumorogenesis. Materials and Methods: In this study, 90 tumor samples from patients diagnosed with DLBCL NOS were evaluated retrospectively. Immunoexpressions of MYC, BCL2, activation-induced cytidine deaminase (AID), uracil-DNA glycosylase (UNG) and DNA mismatch repair proteins including MLH1, MSH2, MSH6 and PMS2 were analyzed. Result: Eleven cases (12.2%) which exhibited >= 40% MYC and >= 50% BCL2 immunexpressions were classified as DEL DLBCL. Patients with MYC positivity displayed lower overall survival rate than MYC negative cases. A trend of lower overall survival was observed in the double-expressor lymphoma group, however, this was not proven to be statistically significant. Significant relationship between AID, UNG and p53 immunexpressions with double-expressor lymphoma or overall survival was not detected. The correlation between immunexpressions of p53 and MYC was observed. 'I'he loss of expression of mismatch repair proteins was not observed in any cases. Conclusion: In this study, a relationship between low overall survival and MYC expression is detected. However, our result does not demonstrate that double-expressor lymphoma can be associated with poor outcomes.
Keywords: Diffuse large B-cell lymphoma; Double-expressor lymphoma; MYC; BCL2; AID; Mismatch repair proteins; INDUCED CYTIDINE DEAMINASE; RITUXIMAB PLUS CYCLOPHOSPHAMIDE; IMMUNOHISTOCHEMICAL BIOMARKERS; MYC REARRANGEMENT; P53 EXPRESSION; C-MYC; SURVIVAL; GENE; BCL2; CLASSIFICATION